The Effect of Ease of Use, Effectiveness, and Perception of Risk on Interest in Using Seabank Digital Bank (A Case Study in Higher Education) - Ramadhani Putri, Habsiah; Trisnaningsih, Sri (IAIN Madura, 2025)
The development of information technology has driven the rapid growth of Financial Technology (Fintech) services, including digital banking. Ease of use, effectiveness, and transaction security have become the main factors encouraging the adoption of these services, especially among Generation Z, who are known for their adaptability to technology. One of the prominent digital banks among students is Seabank, which is recorded as the most widely used digital bank by accounting students at UPN